The Effectiveness of using technology in music teaching at SMK Seri Kuching, Sarawak / Leroy Perez Estor - Estor, Leroy Perez (2015)
The purpose of this study was to analyze the effectiveness of using technology in music teaching at SMK Seni Kuching, Sarawak. On the other hand, I try to investigate the feedback from the teaches towards the usage of technology in music teaching and what can be done to improve in using the technology. Besides, I also focused on the students’ feedbacks on the animdes and experiences in using technology in music learning. They also give feedback about the grades afier learning music using technology. The results show there is strong relationship between technology and music learning.